Differentiation therapy exerts antitumor effects on stem-like glioma cells - Campos, Benito; Wan, Feng; Farhadi, Mohammad Reza; Ernst, Aurélie; Zeppernick, Felix; Tagscherer, Katrin; Ahmadi, Rezvan; Lohr, Jennifer; Dictus, Christine; Gdynia, Georg; Combs, Stephanie; Goidts, Violaine; et al. (Clinical cancer research, 2010)
Purpose: Stem-like tumor cells comprise a highly tumorigenic and therapy-resistant tumor subpopulation, which is believed to substantially influence tumor initiation and therapy resistance in glioma. Currently, therapeutic, drug-induced differentiation is considered as a promising approach to eradicate this tumor-driving cell population; retinoic acid is well known as a potent modulator of differentiation and proliferation in normal stem cells. In glioma, knowledge about the efficacy of retinoic acid-induced differentiation to target the stem-like tumor cell pool could have therapeutic implications.Experimental Design: Stem-like glioma cells (SLGC) were differentiated with all-trans retinoic acid-containing medium to study the effect of differentiation on angiogenesis, invasive growth, as well as radioresistance and chemoresistance of SLGCs. In vivo effects were studied using live microscopy in a cranial window model.Results: Our data suggest that in vitro differentiation of SLGCs induces therapy-sensitizing effects, impairs the secretion of angiogenic cytokines, and disrupts SLGCs motility. Further, ex vivo differentiation reduces tumorigenicity of SLGCs. Finally, we show that all-trans retinoic acid treatment alone can induce antitumor effects in vivo.Conclusions: Altogether, these results highlight the potential of differentiation treatment to target the stem-like cell population in glioblastoma. Clin Cancer Res; 16(10); 2715-28. ©2010 AACR.
Gesehen am 29.03.2023